How probiotic fertilizers improve irrigation efficiency, buffer salts, and reduce nitrate infiltration into groundwater - Martin, Kenneth R., author; Ellsworth, Robert, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1992)
Since the advent of chemical fertilizers there has been a loss of humus in most agricultural soils and a diminishing of the vital biological dynamics which were present in less intensive chemical farming. The loss of healthy top soil is well documented. Salt problems are significant in virtually all irrigation areas, and the deterioration of soil structure with resulting reduction of irrigation efficiency is well-known. Probiotic technology, which takes into account the biological potential of soils, can reverse these trends and enables the farmer to use "environmentally friendly" fertilizers which restore and build healthy soil by increasing the humus complexes in soils. The dramatic change in soil structure improves water infiltration and water release efficiency, and buffers harmful salts in water and soil. University research has shown that nitrate fertilizers can be maintained in the root zone with less leaching of nitrate and other agrichemicals due to biological complexing and chelation. Probiotic technology enhances the natural processes in the soil while biodegrading the detrimental chemical residue that has accumulated in soil. Humus is a biological soil derivative which has received insufficient research attention. The pressure to develop high production agriculture utilizing salt-based fertilizers and a host of chemicals has been the focus of most agricultural research. The residual of many of these compounds has been detrimental to the health and vitality of the natural biological systems. Soil conditions have generally deteriorated. This deterioration contributes to erosion which is responsible for significant losses in fertile soil every year.
Irrigation and water resources in the 1990's
Probiotic fertilizers
Not digitized by CSUL Digital Services.
Presented at Irrigation and water resources in the 1990's: proceedings from the 1992 national conference held on October 5-7, 1992 in Phoenix, Arizona.